Spectral measurement with a linear variable filter using a LMS algorithm - Emadi, Arvin; Grabarnik, S.; Wu, H.; de Graaf, G.; Wolffenbuttel, R.F. (Procedia engineering, 2010)
This paper presents spectral measurements using a linear variable optical filter. A LVOF has been developed for operation in the 530 nm–720 nm spectral band and has been fabricated in an IC-compatible process. The LVOF has been mounted on a CMOS camera. A Least Mean Square algorithm has been implemented to calculate the spectrum of light from the recorded image on the CMOS camera. A spectral resolution of 0.5 nm has been achieved using the algorithm. The spectral resolution is limited by the monochromator accuracy used for calibration.